Obstetric experiences of young black mothers: An intersectional perspective. (January 2023) - OjiNjideka Hemphill, Nefertiti; Crooks, Natasha; Zhang, Wenqiong; Fitter, Fareeha; Erbe, Katherine; Rutherford, Julienne N.; Liese, Kylea L.; Pearson, Pamela; Stewart, Karie; Kessee, Nicollette; Reed, Luecendia; Tussing-Humphreys, Lisa; et al.
Abstract: Background: In Chicago, maternal morbidity and mortality is six times more likely among Black birthing people than white, despite policy initiatives to promote maternal health equity. Disparities in maternal morbidity and mortality reflect experiences of structural inequities – including limited quality obstetric care, implicit bias, and racism resulting patient mistrust in the health care system, inadequate social support, and financial insecurity. Although there is published literature on Black women's experiences with obstetric care, including experiences with individual and structural racism, little is known about the intersection of age and race and experiences with health care. The purpose of this study was to explore the maternal health and pregnancy experiences of young Black women utilizing an intersectional theoretical lens. Methods: In this study, we conducted two focus groups in a sample of 11 young Black pregnant people. We conducted a thematic analysis to identify codes, themes, and subthemes of the data. Results: We developed two overarching themes: obstetric racism and obstetric resistance. To elucidate how obstetric racism framed our participants' healthcare experiences, we identified sub-themes: intersectional identities as young Black women, medical mistrust, and pregnancy trauma. The second major theme describes ways in which participants protected themselves against obstetric racism to engender positive health experiences. These methods of resistance included identifying advocates and relying on trusted providers. Conclusions: The current standard of obstetric care in the US is suboptimal due to individual and structural racism. This study provides unique data on the experiences with health care for young, Black pregnant individuals and delivers valuable insight into how individual and structural racism impacts obstetric care for young Black women. Highlights: Little is known about the intersection between race and age in prenatal care experience. Participants felt their concerns were dismissed and mistrusted their providers. Women were disenfranchised with their healthcare experiences. Practitioners should affirm and create conditions for healing for young Black women.